Endophytic Paecilomyces formosus LHL10 Augments Glycine max L. Adaptation to Ni-Contamination through Affecting Endogenous Phytohormones and Oxidative Stress - Bilal, Saqib; Khan, Abdul L.; Shahzad, Raheem; Asaf, Sajjad; Kang, Sang-Mo; Lee, In-Jung (Frontiers in Plant Science, 2017)
This study investigated the Ni-removal efficiency of phytohormone-producing endophytic fungi Penicillium janthinellum, Paecilomyces formosus, Exophiala sp., and Preussia sp. Among four different endophytes, P. formosus LHL10 was able to tolerate up to 1 mM Ni in contaminated media as compared to copper and cadmium. P. formosus LHL10 was further assessed for its potential to enhance the phytoremediation of Glycine max (soybean) in response to dose-dependent increases in soil Ni (0.5, 1.0, and 5.0 mM). Inoculation with P. formosus LHL10 significantly increased plant biomass and growth attributes as compared to non-inoculated control plants with or without Ni contamination. LHL10 enhanced the translocation of Ni from the root to the shoot as compared to the control. In addition, P. formosus LHL10 modulated the physio-chemical apparatus of soybean plants during Ni-contamination by reducing lipid peroxidation and the accumulation of linolenic acid, glutathione, peroxidase, polyphenol oxidase, catalase and superoxide dismutase. Stress-responsive phytohormones such as abscisic acid and jasmonic acid were significantly down-regulated in fungal-inoculated soybean plants under Ni stress. LHL10 Ni-remediation potential can be attributed to its phytohormonal synthesis related genetic makeup. RT-PCR analysis showed the expression of indole-3-acetamide hydrolase, aldehyde dehydrogenase for indole-acetic acid and geranylgeranyl-diphosphate synthase, ent-kaurene oxidase (P450-4), C13- oxidase (P450-3) for gibberellins synthesis. In conclusion, the inoculation of P. formosus can significantly improve plant growth in Ni-polluted soils, and assist in improving the phytoremediation abilities of economically important crops.